Revision of the Indo-Pacific cardinalfish genus Siphamia (Perciformes: Apogonidae) - Gon, Ofer; Allen, Gerald R. (Zootaxa, 2012)
The Indo-Pacific apogonid genus Siphamia Weber 1909 is unique among cardinalfishes in having a bacterial biolumines-cent system and spinoid scales. Light is produced by luminous bacteria found in a small pocket connected to the gut in theabdominal cavity and in a sac on each side of the tip of the tongue. Siphamia consists of 23 small species many of whichare associated with invertebrates such as sea urchins, crown-of-thorns starfish and coral. Species of this genus fall intotwo main groups with different dark pigment pattern of the longitudinal translucent muscle acting as a light organ thatdiffuses light along the ventral edge of the body. The S. tubifer group, with a striated light organ, includes S. arabica, newspecies, from the Gulf of Oman; S. argentea from the Philippines and northern Western Australia; S. fraseri, new species,from New Caledonia, Tonga and Fiji; S. fuscolineata from the Marshall and Line islands; S. goreni, new species, from thesouthern Red Sea; S. guttulata from Darnley Island, Queensland; S. jebbi from the western Pacific, ranging from the Phil-ippines to Western Australia and east to the Caroline Islands, Fiji, and Tonga; S. majimai from the Ryukyu and Ogasawaraislands to northwestern Australia, ranging eastward to New Caledonia and Tonga; S. mossambica from the western IndianOcean; S. randalli, new species, from the Society and Cook islands; S. spinicola, new species, from Biak in eastern Indo-nesia, Papua New Guinea, Woleai Atoll, Vanuatu, New Caledonia and the Chesterfield Islands; S. stenotes, new species,from the Triton Bay area of Irian Jaya Barat Province of Indonesia; and S. tubifer ranging widely in the Indo-West Pacificfrom the Red Sea to Madagascar and east to Vanuatu. The S. tubulata group, with a dark-dotted light organ, includes S.brevilux, new species, from Papua New Guinea; S. cephalotes from southern Australia; S. corallicola from Indonesia, Sa-bah, and Timor Sea; S. cuneiceps from Western Australia and the east coast of Queensland; S. cyanophthalma, new species,from the Philippines, Palau, Indonesia, and Papua New Guinea; S. elongata from the Philippines and Brunei; S. fistulosafrom Java, Sumbawa and Komodo, Indonesia, and Brunei; S. roseigaster from Western Australia, ranging along the north-ern and eastern coast of Australia south to Sydney Harbour, New South Wales; S. senoui, new species, from the RyukyuIslands, Japan; and S. tubulata from the Papua Barat Province, Indonesia, south coast of Papua New Guinea, northern Western Australia and Queensland.